Avaliação dos efeitos comportamentais e neuroquímicos induzidos por diferentes doses de reserpina em camundongos - Freitas, Catiuscia Molz de (2014)
Reserpine administration is considered an animal model for the study of tardive dyskinesia by some authors and a model for the study of parkinsonism by others. However, despite several studies used this model to assess the potential of substances to treat these movement disorders, little is known about the mechanisms involved in the development of behavioral changes in reserpine model. Thus, the present study investigated whether behavioral alterations induced by reserpine are related to alterations in dopaminergic system proteins as tyrosine hydroxylase (TH), dopamine transporter (DAT) and monoaminoxidase (MAO). For this, reserpine was administered subcutaneously in mice at doses of 0.1, 0.5 or 1 mg / kg or vehicle (0.2% acetic acid in NaCl 0.9%) for 4 consecutive days. The number of vacuous chewing movements (VCMs), exploratory and locomotor activity were assessed 48 hours (6th day) and 20 days (24th day) after withdrawal of treatment in order to evaluate the induction and maintenance of motor disorders caused by reserpine. It was also analyzed the TH and DAT immunoreactivity by Western blot and the MAO-A and MAO-B activity in striatum and region containing substantia nigra on days 6 and 24. Treatment with 1 mg/kg reserpine caused an increase in VCMs and hypolocomotion in animals, and this effect remained for at least 20 days after withdrawal of reserpine. These alterations were accompanied by a reduction in striatal DAT immunoreactivity and a reduction of TH immunoreactivity in the substantia nigra evaluated on day 6. On the 24th day was observed a decrease in the DAT and TH immunoreactivity in both striatum and substantia nigra. The dose of 0.5 mg/kg reserpine caused behavioral alterations on day 6, but these changes were not maintained after withdrawal of treatment and also neurochemical changes not were found at this dose. We did not find any statistical differences when behavioral and neurochemical parameters were evaluated at a dose of 0.1 mg/kg reserpine. Thereby, these results suggest that reserpine causes changes in dopaminergic system proteins which lead to motor alterations. Thus, possible pharmacological interventions in these proteins could ameliorate motor symptoms in both, Parkinson's disease and tardive dyskinesia.